2004
DOI: 10.1080/03079450400013147
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evidence that the MHC (B haplotype) of chickens influences genetic resistance to attenuated infectious bronchitis vaccine strains in chickens

Abstract: Infectious bronchitis is a respiratory disease of chickens that is caused by the coronavirus infectious bronchitis virus (IBV). Virtually all broiler and layer breeder flocks are routinely vaccinated against IBV. Two hatches of 1-day-old chicks from four lines were mistakenly vaccinated for infectious bronchitis using a moderately attenuated vaccine designed for chicks of an older age. The vaccination resulted in high mortality, and chicks from three of four lines died with signs typical of infectious bronchit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Monocytes derived from additional homozygous MHC haplotypes were also differentially activated by IFNγ. The cells purified from B15/B15 birds, which were shown by Bacon et al (2004) to be more resistant to IBV infection also demonstrated greater macrophage stimulation. It is possible that genes lying outside this region could also affect macrophage activation as demonstrated in other lines.…”
Section: Discussionmentioning
confidence: 90%
“…Monocytes derived from additional homozygous MHC haplotypes were also differentially activated by IFNγ. The cells purified from B15/B15 birds, which were shown by Bacon et al (2004) to be more resistant to IBV infection also demonstrated greater macrophage stimulation. It is possible that genes lying outside this region could also affect macrophage activation as demonstrated in other lines.…”
Section: Discussionmentioning
confidence: 90%
“…It is suspected that the underlying cause of the difference is immunological. There is evidence for the MHC haplotype of chickens influencing genetic resistance to IBV [2].…”
Section: Variation In Host Susceptibility To Ibvmentioning
confidence: 99%
“…The capacity of the virus to replicate in so many tissues may contribute to the sequence diversity of its proteins, especially that of the S protein. Strains of IBV differ in their virulence, and the genetic background of the host can influence the outcome of infection (see Bacon et al ., 2004, and references cited therein). Thus, IBV is not a simple pathogen and its heterogeneity with respect to its protein sequences, broad tissue tropism and pathogenicity should be borne in mind in the context of the host range of the virus, which, as described later, may be wide.…”
Section: S Nmentioning
confidence: 99%